Pembagian Harta Tak Bergerak Akibat Perceraian Berdasarkan Putusan Nomor 149/Pdt.G/2017/Pn Tabanan - Anak Agung Istri Altia Dwi Widaswari; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
The law of husband and wife wealth due to divorce is joint property and must be divided by 50% for husband and wife. equitable distribution of shared assets, a dispute will arise between the two. If the joint property is in the form of immovable objects, the parties maintain their share rights without anyone intending to relinquish their rights to be sold to other parties, how to resolve it. The purposes of this study are to describe the distribution of property in the form of immovable objects after divorce in the absence of a marriage agreement and the judge's considerations in determining the distribution of marital property on immovable objects between husband and wife after divorce in the absence of a marriage agreement. The research method used is normative legal research with a statutory approach. Researchers obtain the required legal materials through recording and documentation studies. The sources of legal materials used are primary and secondary sources of legal materials. Then, the legal materials and data are managed using interpretation analysis. The results of the study reveal that the distribution of assets after divorce in the absence of a marriage agreement can be done through mediation or through the courts. Regarding the distribution of assets in the decision Number 149/Pdt.G/2017, it is in accordance with the evidence, facts at trial. The author suggests judges to be more careful in deciding cases. for the legislature must continue to revise the law in order to follow the development of society.